High‐Energy Storage Performance in (Pb0.98La0.02)(Zr0.45Sn0.55)0.995O3 AFE Thick Films Fabricated via a Rolling Process. Issue 11 (28th July 2016) - Wang, Xiucai; Yang, Tongqing; Shen, Jie
Abstract : (Pb0.98 La0.02 )(Zr0.45 Sn0.55 )0.995 O3 antiferroelectric (AFE) thick films with a thickness of about 85 μm were successfully fabricated via a rolling process using an improved sintering method, and all specimens showed high‐energy‐storage performance. The X‐ray diffraction, SEM pictures, and hysteresis loops confirmed that the sintering temperature had an important influence on the microstructures, dielectric properties and energy storage performance of AFE thick films. The grain size and the storage efficiency increased with the increasing sintering temperature, the energy storage performance was enlarged by the rolling process. As a result, a maximum recoverable energy density of 7.09 J/cm 3 with an efficiency of 88% was achieved at room temperature, together with stable energy‐storage behavior, which was almost three times higher than that (2.43 J/cm 3 ) of the bulk ceramics counterparts. The results demonstrated that the improved method was an effective way to improve the breakdown strength and energy storage performance of AFE thick films, and (Pb0.98 La0.02 )(Zr0.45 Sn0.55 )0.995 O3 AFE thick films were a promising material for high‐power energy storage.